Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754700
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining 2-Approximations for the Dynamic Vertex Cover Problem Using Evolutionary Algorithms

Abstract: Evolutionary algorithms have been frequently used to deal with dynamic optimization problems, but their success is hard to understand from a theoretical perspective. With this paper, we contribute to the theoretical understanding of evolutionary algorithms for dynamic combinatorial optimization problems. We examine a dynamic version of the classical vertex cover problem and analyse evolutionary algorithms with respect to their ability to maintain a 2-approximation. Analysing the different evolutionary algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 11 publications
1
46
0
Order By: Relevance
“…A dynamic change affects the graph by either deleting an edge or adding it. However, it is already shown that (1+1) EA e restores the quality of 2-approximation when a new edge is added dynamically in expected time O(m) [16]. In Theorem 8 we prove that the expected re-optimisation time of (1+1) EA e after a dynamic deletion is also O(m).…”
Section: Improving Re-optimisation Time Of the (1+1) Ea For Dynamic Vmentioning
confidence: 72%
See 3 more Smart Citations
“…A dynamic change affects the graph by either deleting an edge or adding it. However, it is already shown that (1+1) EA e restores the quality of 2-approximation when a new edge is added dynamically in expected time O(m) [16]. In Theorem 8 we prove that the expected re-optimisation time of (1+1) EA e after a dynamic deletion is also O(m).…”
Section: Improving Re-optimisation Time Of the (1+1) Ea For Dynamic Vmentioning
confidence: 72%
“…In this paper, we have investigated the behaviour of two simple randomised search heuristics, namely RLS and (1+1) EA, on the dynamic vertex cover problem. The expected required time for re-optimization of the classical vertex cover problem after a dynamic change had been analysed in [16] for these two algorithms with an edge-based representation. In this paper we have improved the results of the analysis of (1+1) EA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(More details of the LP formulation and its dual formulation for the fractional WVC can be found in the next section. ) Pourhassan et al [22] presented a dynamic model of the Vertex Cover problem, in which the graph-editing operation adds (resp., removes) exactly one edge into (resp., from) the given unweighted graph, and analyzed evolutionary algorithms with respect to their abilities to maintain a 2-approximate solution. They examined different variants of the RLS and (1+1) EA, node-based representation and edge-based representation.…”
Section: Introductionmentioning
confidence: 99%